2012
DOI: 10.1088/0004-637x/746/1/30
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Evolution of a Multi-Threaded Solar Prominence

Abstract: We investigate the process of formation and subsequent evolution of prominence plasma in a filament channel and its overlying arcade. We construct a three-dimensional time-dependent model of an intermediate quiescent prominence suitable to be compared with observations. We combine the magnetic field structure with one-dimensional independent simulations of many flux tubes, of a three-dimensional sheared double arcade, in which the thermal nonequilibrium process governs the plasma evolution. We have found that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
115
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(135 citation statements)
references
References 63 publications
20
115
0
Order By: Relevance
“…Due to the strong strapping field (cyan field lines) overhead, the expanding sheared field increasingly stretches out to develop a quite flat midsection above the PIL (see also Antiochos et al 1994;DeVore & Antiochos 2000Aulanier et al 2002). Using 1D models with comprehensive descriptions of the thermodynamics, Karpen et al (2001Karpen et al ( , 2005 have shown that such regions can host long-lived condensations that resemble cool, counterstreaming filament plasma (see also Luna et al 2012). Over time, the null point above the strapping field becomes increasingly compressed, and a breakout current sheet (BCS; Figure 4(b)) forms there.…”
Section: Jet Mechanismmentioning
confidence: 99%
“…Due to the strong strapping field (cyan field lines) overhead, the expanding sheared field increasingly stretches out to develop a quite flat midsection above the PIL (see also Antiochos et al 1994;DeVore & Antiochos 2000Aulanier et al 2002). Using 1D models with comprehensive descriptions of the thermodynamics, Karpen et al (2001Karpen et al ( , 2005 have shown that such regions can host long-lived condensations that resemble cool, counterstreaming filament plasma (see also Luna et al 2012). Over time, the null point above the strapping field becomes increasingly compressed, and a breakout current sheet (BCS; Figure 4(b)) forms there.…”
Section: Jet Mechanismmentioning
confidence: 99%
“…Three kinds of models have been proposed. Filament plasma can be formed by condensation of coronal material along magnetic field lines, which may be accumulated in coronal cavities (Karpen et al 2005;Luna et al 2012;Berger et al 2010Berger et al , 2012. A filament may be lifted Two movies are available in electronic form at http://www.aanda.org through the photosphere by a levitation process (Okamoto et al 2008;Lites et al 2010) or formed by successive reconnections between magnetic field lines (van Ballegooijen & Martens 1989;Schmieder et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Karpen et al 2003). Based on the simulations by Luna et al (2012b) and the results by Karpen et al (2005) we can estimate that the speed of the hot flows is of the order of 30 km s −1 . We also take a typical value of ζ = 100 (see Labrosse et al 2010).…”
Section: Prominence Oscillations In a Magnetic Tube With Two Straightmentioning
confidence: 88%